Nexusing Charcoal in South Mozambique: A Proposal To Integrate the Nexus Charcoal-Food-Water Analysis With a Participatory Analytical and Systemic Tool - Martins, Ricardo (Frontiers in Environmental Science, 2018)
Nexus analysis identifies and explores the synergies and trade-offs between energy, food and water systems, considered as interdependent systems interacting with contextual drivers (e.g. climate change, poverty). The nexus is, thus, a valuable analytical and policy design supporting tool to address the widely discussed links between bioenergy, food and water. In fact, the Nexus provides a more integrative and broad approach in relation to the single isolated system approach that characterises many bioenergy analysis and policies of the last decades. In particular, for the South of Mozambique, charcoal production, food insecurity and water scarcity have been related in separated studies and, thus, it would be expected that Nexus analysis has the potential to provide the basis for integrated policies and strategies focused on charcoal as a development factor. However, to date there is no Nexus analysis focused on charcoal in Mozambique, neither is there an assessment of the comprehensiveness and relevance of Nexus analysis when applied to charcoal energy systems. To address these gaps, this work applies the Nexus to the charcoal-food-water system in Mozambique, integrating national, regional and international studies analysing the isolated, or pairs of, systems. This integration results in a novel Nexus analysis graphic for charcoal-food-water relationship. Then, to access the comprehensiveness and depth of analysis, this Nexus analysis is critically compared with the 2MBio-A, a systems analytical and design framework based on a design tool specifically developed for Bioenergy (the 2MBio). The results reveal that Nexus analysis is “blind” to specific fundamental social, ecological and socio-historical dynamics of charcoal energy systems. The critical comparison also suggests the need to integrate the high level systems analysis of Nexus with non-deterministic, non-prescriptive participatory analysis tools, like the 2MBio-A, as a means to increase sensitivity to the specifics of charcoal systems while keeping the practical benefits of Nexus as a high level policy design tool. In conceptual terms, this integration promotes open, participatory, integrated, comprehensive and creative analysis and exploration of the Nexus across scales, disciplines and sectors, providing thus, a strong base to design inclusive, sound and robust policies, projects and strategies relating/integrating charcoal, food and water security.